Making myself understood: perceived factors affecting the intelligibility of sung text - Fine, Philip A.; Ginsborg, Jane (Frontiers in Psychology, 2014)
Singing is universal, and understanding sung words is thought to be important for many listeners’ enjoyment of vocal and choral music. However, this is not a trivial task, and sung text intelligibility is probably affected by many factors. A survey of musicians was undertaken to identify the factors believed to have most impact on intelligibility, and to assess the importance of understanding sung words in familiar and unfamiliar languages. A total of 143 professional and amateur musicians, including singers, singing teachers and regular listeners to vocal music, provided 394 statements yielding 851 references to one or more of 43 discrete factors in four categories: performer-related, listener-related, environment-related and words/music-related. The factors mentioned most frequently in each of the four categories were, respectively: diction; hearing ability; acoustic; and genre. In more than a third of references, the extent to which sung text is intelligible was attributed to the performer. Over 60% of respondents rated the ability to understand words in familiar languages as “very important”, but only 17% when the text was in an unfamiliar language. Professional musicians (47% of the sample) rated the importance of understanding in both familiar and unfamiliar languages significantly higher than amateurs but listed fewer factors overall and fewer listener-related factors. The more important the respondents rated understanding, the more performer-related and environment-related factors they tended to list. There were no significant differences between the responses of those who teach singing and those who do not. Enhancing sung text intelligibility is thus perceived to be within the singer’s control, at least to some extent, but there are also many factors outside their control. Empirical research is needed to explore some of these factors in greater depth, and has the potential to inform pedagogy for singers, composers and choral directors.